Coitus Interruptus: Sex, Bram Stoker, and Dracula - Miller, Elizabeth (Romanticism on the Net)

(untitled) (Université de Montréal, 2006)
AbstractReaders of Dracula have been assured repeatedly that the novel is all about sex. Indeed, every sexual practice, fantasy and fear imaginable has been thrust upon its pages: rape (including gang rape), aggressive female sexuality, fellatio, homoeroticism, incest, bestiality, necrophilia, pedophilia, and sexually transmitted disease. Words have been twisted to yield new meanings, passages have been examined out of context, and gaps in the text have been declared intentional omissions. Furthermore, critics comb every aspect of Stoker’s life looking for evidence for their particular brand of psychosexual analysis, sometimes even inventing “facts” to support flimsy theories. The preponderance of such readings of Dracula demands re-assessment. While it would be folly to deny any erotic content in a novel about biting and sucking, the incessant pursuit of this path has led us down the slippery slope of revisionist biography and reductive textual nit-picking. Such readings may be a product of the late twentieth century’s voyeuristic obsession with sexuality, coupled with a determination to project (sometimes in condescending fashion) its own self-proclaimed sophisticated and liberated views onto a Victorian text - and its author.